2013
DOI: 10.1093/annonc/mdt116
|View full text |Cite
|
Sign up to set email alerts
|

FOLFOX4 plus cetuximab administered weekly or every second week in the first-line treatment of patients with KRAS wild-type metastatic colorectal cancer: a randomized phase II CECOG study

Abstract: Activity and safety of FOLFOX4 plus either cetuximab administered weekly or every second week were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 32 publications
12
48
1
Order By: Relevance
“…The authors concluded that the activity and safety of FOLFOX plus either cetuximab administered weekly or biweekly were similar. [18] In the Medical Research Council COIN trial, 1,630 patients were randomly assigned to treatment groups: 815 to oxaliplatin and 5 FU chemotherapy (FOLFOX or XELOX; arm A) and 815 to the same combinations plus cetuximab (arm B). Tumour samples from 1,316 (81%) patients were used for somatic molecular analyses; 565 (43%) had K-RAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the activity and safety of FOLFOX plus either cetuximab administered weekly or biweekly were similar. [18] In the Medical Research Council COIN trial, 1,630 patients were randomly assigned to treatment groups: 815 to oxaliplatin and 5 FU chemotherapy (FOLFOX or XELOX; arm A) and 815 to the same combinations plus cetuximab (arm B). Tumour samples from 1,316 (81%) patients were used for somatic molecular analyses; 565 (43%) had K-RAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Biweekly administration is not included in the SPC for cetuximab. We consider the RCT by Brodowicz et al 166 to be of sufficient quality to make this claim and believe the claim of equivalence to be reasonable.…”
Section: Drug Acquisition Costsmentioning
confidence: 91%
“…Cetuximab was assumed to be administered on a biweekly schedule to coincide with FOLFOX/FOLFIRI administration, as this is common clinical practice within the NHS. In addition, Merck Serono argued, on the basis of an open-label RCT by Brodowicz et al 166 and a literature review, 167 that biweekly administration of 500 mg/m 2 of cetuximab is equivalent to induction with 400 mg/m 2 followed by weekly administration of 250 mg/m 2 . Biweekly administration is not included in the SPC for cetuximab.…”
Section: Drug Acquisition Costsmentioning
confidence: 99%
“…In clinical studies performed in mCRC, biweekly cetuximab up to 700 mg/m 2 (q2w) showed a safety profile similar to that described for the weekly administration [18]. Overall, different clinical studies (a phase I study, several controlled and non-controlled phase II studies, and retrospective studies) concluded that in patients with mCRC, cetuximab q2w combined with chemotherapy (CT) regimens was feasible and may be as effective and safe as the standard weekly schedule [13,20,21].…”
Section: Discussionmentioning
confidence: 92%